2011
DOI: 10.1007/s10646-011-0696-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic metal exposure on wild fish populations revealed by high-throughput cDNA sequencing

Abstract: Given the inherent variability of aquatic systems, predicting the in situ effects of contaminants on such ecosystems still represents a major challenge for ecotoxicology. In this context, transcriptomic tools can help identify and investigate the mechanisms of toxicity beyond the traditional morphometric, physiological and population-level endpoints. In this study, we used the 454 sequencing technology to examine the in situ effects of chronic metal (Cd, Cu) exposure on the yellow perch (Perca flavescens) tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 40 publications
1
33
1
4
Order By: Relevance
“…These results suggest that in mussels located downstream from the polluted site, immune system and oxidative stress defenses were impacted. In fish, the transcription of genes encoding proteins involved in immunity is often negatively correlated to metal concentrations (Williams et al 2006;Reynders et al 2006;Pierron et al 2011). Studies in bivalves are less abundant and reported little or no effect in Cerastoderma edule (Paul-Pont et al 2010) and an increase in hemocyte density in Mytilus edulis (Coles et al 1995) and Crassostrea gigas (Auffret and Oubella 1994).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that in mussels located downstream from the polluted site, immune system and oxidative stress defenses were impacted. In fish, the transcription of genes encoding proteins involved in immunity is often negatively correlated to metal concentrations (Williams et al 2006;Reynders et al 2006;Pierron et al 2011). Studies in bivalves are less abundant and reported little or no effect in Cerastoderma edule (Paul-Pont et al 2010) and an increase in hemocyte density in Mytilus edulis (Coles et al 1995) and Crassostrea gigas (Auffret and Oubella 1994).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of knowledge about this role precludes any further interpretation regarding a potential alteration of retinoid metabolism or adipose tissue physiology. However, an impairment in retinol metabolism and its impacts on lipid and energy metabolisms were identified as a potential mechanism of metal toxicity in fish (Pierron et al 2011;Defo et al 2012). Downstream mussels may experience deleterious effects on renal physiology as NHE transporters are involved in renal phosphate reabsorption.…”
Section: Resultsmentioning
confidence: 99%
“…We prepared cDNA libraries for 454 sequencing following the protocol described in Pierron et al (2011). Two samples of 20 glass eels were collected just prior to settlement in freshwater at two river mouths located near the extreme ends of the species' latitudinal range: the Grande Rivière Blanche in the lower St. Lawrence estuary (RB, 48°789N, 67°709W) and Florida (FL, 30°009N, 81°199W).…”
Section: Methodsmentioning
confidence: 99%
“…These identified differential expressed miRNAs may have the potential as biomarkers for other fish species as well. Other similar studies using RNA-seq were carried out in brown trout (Salmo trutta) (Uren Webster et al, 2013), Gulf killifish (Fundulus grandis) , and yellow perch (Perca flavescens) (Pierron et al, 2011) stressed by a mixture copper and zinc, deepwater horizon oil, and a mixture cadmium and copper, respectively. In general, these studies have successfully shown that RNA-seq is a powerful approach to study the ecotoxicological response of fish to the polluted environments.…”
Section: Quantifying Transcript Levelmentioning
confidence: 98%